2004
DOI: 10.1088/0957-4484/15/11/044
|View full text |Cite
|
Sign up to set email alerts
|

Injection moulding of high aspect ratio micron-scale thickness polymeric microcantilevers

Abstract: Tipless thermoplastic microcantilevers suitable for chemical and biological sensing applications were fabricated by injection moulding. Their stiffnesses and resonant frequencies were each determined by two techniques. Polystyrene beams produced by this method exhibited stiffnesses ranging from 0.01 to 10 N m−1, making them feasible for biosensing applications. The approach proved repeatable with low standard deviations on the parameters measured on 22 microcantilever beams (stiffness and first-mode resonant f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
29
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(29 citation statements)
references
References 19 publications
0
29
0
Order By: Relevance
“…[117,118] In other study, Layer-by-Layer (LBL) technique, which offers nanometer control over the thickness of the polymer films, has proven to provide a multitude of soft free standing micromechanical structures with high degree of mechanical integrity and flexibility and very minute thickness unachievable by common microfabrication procedures. [17,73,119] LBL assembly of polycations, clay, and magnetite nanoparticles employed in this study produced 170 nm thick free standing composite cantilevers, which could be actuated by a magnetic field.…”
Section: Fabrication Of Microcantileversmentioning
confidence: 99%
“…[117,118] In other study, Layer-by-Layer (LBL) technique, which offers nanometer control over the thickness of the polymer films, has proven to provide a multitude of soft free standing micromechanical structures with high degree of mechanical integrity and flexibility and very minute thickness unachievable by common microfabrication procedures. [17,73,119] LBL assembly of polycations, clay, and magnetite nanoparticles employed in this study produced 170 nm thick free standing composite cantilevers, which could be actuated by a magnetic field.…”
Section: Fabrication Of Microcantileversmentioning
confidence: 99%
“…For ultra‐thin cavities, there is very little systematic research. Most of the studies available today that are related to micro‐features transcription in micro‐injection are focused on the micro‐structural6 parts with large depth/width ratio or with some special functions such as micro‐channel, micro‐lens, or micro‐grating 7. These micro‐parts have only micro‐features on single surface 8.…”
Section: Introductionmentioning
confidence: 99%
“…They confirmed that the injection pressure in a heated isothermal mold cavity decreases as the injection speed decreases and therefore extremely thin parts can be molded at lower injection speeds. McFarland et al 66 reported that, by using a rapidly heated mold at a mold temperature of 205…”
Section: Lengthening Flow Pathmentioning
confidence: 99%
“…The thermal performance of these small molds can be further improved by judicious engineering design of the mold. 66,67 This article attempts to offer, to some extent, a constructive overview on the state of the art in mold rapid heating and cooling, aiming at explaining the working mechanisms and providing an unbiased account of the pros and cons of existing processes and techniques. Successful applications of existing processes are highlighted and potential improvements to these processes are suggested.…”
mentioning
confidence: 99%